Թեյշեբաինիի ձկնակերպ կավե արձանիկների կերպարային լուծումներն ու ծիսական նշանակությունը - Գայանե Պողոսյան (ՀՀ ԳԱԱ հրատ.)
В искусстве Ванского царства от традиционных урартийских изобразительных форм резко отличаются три глиняные рыбообразные статуэтки из Тейшебаини. Эти статуэтки малых форм изготовлены из рыжеватой глины,высотой около 15 см. Статуэтки однообразны, представляют стоящие борода- тые фигуры антропоморфных божеств, со схематически изображенными чертами лиц, условными частями тела и остатками синей краски на спинах.In the art of the Van Kingdom, three clay fish-like statuettes from Teyshebaini are different from the traditional Urartian artistic forms. These small figurines are made of reddish clay, about 15 cm high. The statuettes are monotonous, representing standing bearded figures of anthropomorphic deities, with schematically illustrated facial features, conventional body parts and the remnants of blue paint on their backs.
Keywords: Religion; Cults; Practical Theology; Liturgy and Ritual; Ancient History; Ceramics